Listen up, kids! How mind wandering affects immediate and delayed memory in children. - Cherry, Jessica; McCormack, Teresa; Graham, Agnieszka J. (Memory & Cognition, 2024)
Mind wandering occurs when attention becomes disengaged from the here-and-now and directed toward internally generated thoughts; this is often associated with poorer performance on educationally significant tasks. In this study, 8- to 9-year-old children (N = 60) listened to audio stories embedded with intermittent thought probes that were used to determine if participants' thoughts were on or off task. The key objective was to explore the impact of probe-caught mind wandering on both immediate and delayed memory retention. Children reported being off task approximately 24% of the time. Most inattention episodes were classified as task-unrelated thoughts (i.e., 'pure' instances of mind wandering, 9%) or attentional failures due to distractions (9%). Higher frequency of mind wandering was strongly associated with poorer memory recall, and task-unrelated thoughts strongly predicted how well children could recall components of the audio story both immediately after the task and after a 1-week delay. This study is the first to demonstrate the impact of mind wandering on delayed memory retention in children. Results suggest that exploring mind wandering in the foundational years of schooling could provide the necessary empirical foundation for the development of practical interventions geared toward detecting and refocusing lapses of attention in educational contexts.